Konsep Iri Dalam Relasi Sosial - Tara’u, Dwi Preti Natalia; Ngguna, Yakin; Yakobus, I Ketut (Fakultas Ekonomi Universitas KristenTentena, 2024)
Envy is a concept that in everyday life is often referred to as 'liver disease'. Envy is considered harmful to social relationships. As an emotion, envy is certainly inevitable. There are various aspects that can cause a person to be envious of others. However, how do people generally understand envy? The purpose of this study is to explore the concept of envy as an emotion to get initial information. The design of this study is an exploratory research using a qualitative grounded theory approach. The research subjects are students and employees with an age range of 20-25 years totaling 13 people. The data collection method was an open questionnaire and the data was analyzed using Strauss and Corbin coding techniques. The results of the study show that envy is defined as a feeling of dissatisfaction with other people's lives, related to feelings of dislike with other people's advantages, and related to feelings of dissatisfaction. Envy does not damage social relationships, but an envious person does not want to open up about feeling jealous of friends, friends, or other people they are jealous of.